2012
DOI: 10.1016/j.ajpath.2012.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Vasculogenic Mimicry

Abstract: In 1999, The American Journal of Pathology published an article entitled "Vascular channel formation by human melanoma cells in vivo and in vitro: vasculogenic mimicry," by Maniotis and colleagues, which ignited a spirited debate for several years and earned distinction as a citation classic. Tumor cell vasculogenic mimicry (VM) refers to the plasticity of aggressive cancer cells forming de novo vascular networks, which thereby contribute to perfusion of rapidly growing tumors, transporting fluid from leaky ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
159
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(161 citation statements)
references
References 61 publications
0
159
0
2
Order By: Relevance
“…Question marks indicate the potential involvement of a protein and/or downstream effector protein or proteins in modulating VM in aggressive cancer cells, for which the underlying signaling pathway or pathways are not yet clearly defined. (Redrawn and modified from Seftor et al, 2012. )…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Question marks indicate the potential involvement of a protein and/or downstream effector protein or proteins in modulating VM in aggressive cancer cells, for which the underlying signaling pathway or pathways are not yet clearly defined. (Redrawn and modified from Seftor et al, 2012. )…”
Section: Figmentioning
confidence: 99%
“…Furthermore, recent studies have shown the tumor origin of endothelial-like cells in specific cancers (Ricci-Vitiani et al, 2010; Wang et al, 2010), further illuminating a genetically unstable and heterogeneous vasculature. Most compelling is the resistance of tumor cell VM to the majority of conventional therapies, thus emphasizing the need for new targeting approaches based on robust molecular findings (van de Schaft et al, 2004; Seftor et al, 2012; Kirschmann et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Release of heparan sulphate-sequestered vascular endothelial growth factor (VEGF) by MMP-9 triggers the angiogenic switch in pancreatic and colorectal cancer models (80, 81); in these models, the tumor-promoting MMP-9 was provided by circulating macrophages and neutrophils. MMP-14 and MMP-2 have been implicated in vasculogenic mimicry (82), a process in which blood and nutrients can reach deep into the tumor through channels that link to new vessels closer to the tumor surface (83). Macrophage-derived MMP-9 was also found to be specifically required for induction of vasculogenesis in animal models, the production of new vessels from progenitor cells derived from the bone marrow (84).…”
Section: Tumorigenic Processes Activated By Mmps In Breast Cancermentioning
confidence: 99%
“…Ultrastructural analysis of these networks revealed a remarkable similarity between tumor cell-formed vessels versus endothelial lined vessels, with the exception of the basement membrane lining (13). In tumor cellformed vessels, blood passes through basement membrane-lined vascular networks with tumor cells sitting exterior to the membrane matrix, while traditional vessels support blood flowing through endothelial cells lining the vasculature with the basement membrane exterior to the cells.…”
Section: Melanoma Vascular Phenotypementioning
confidence: 99%